Honduras : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2005)
Honduras's Report on the Observance of Standards and Codes highlights Data Module, response by the authorities, and detailed assessments using the data quality assessment framework. Meeting General Data Dissemination System (GDDS) recommendations will also require disseminating production indices. To follow GDDS recommendations and facilitate eventual subscription to the Special Data Dissemination Standard, it would be important that key agencies move in the future with plans for improvement. To participate in the GDDS, the authorities would need to appoint a GDDS coordinator and commit to follow GDDS recommendations for selected data.